New measurements on water ice photodesorption and product formation under ultraviolet irradiation. Issue 3 (17th November 2017) - Cruz-Diaz, Gustavo A; Martín-Doménech, Rafael; Moreno, Elena; Muñoz Caro, Guillermo M; Chen, Yu-Jung
Abstract: The photodesorption of icy grain mantles has been claimed to be responsible for the abundance of gas-phase molecules towards cold regions. Being water a ubiquitous molecule, it is crucial to understand its role in photochemistry and its behaviour under an ultraviolet field. We report new measurements on the ultraviolet (UV) photodesorption of water ice and its H2, OH, and O2 photoproducts using a calibrated quadrupole mass spectrometer. Solid water was deposited under ultra-high-vacuum conditions and then UV-irradiated at various temperatures starting from 8 K with a microwave discharged hydrogen lamp. Deuterated water was used for confirmation of the results. We found a photodesorption yield of 1.3 × 10 −3 molecules per incident photon for water and 0.7 × 10 −3 molecules per incident photon for deuterated water at the lowest irradiation temperature, 8 K. The photodesorption yield per absorbed photon is given and comparison with astrophysical scenarios, where water ice photodesorption could account for the presence of gas-phase water towards cold regions in the absence of a thermal desorption process, is addressed.